Quasi-Static Linear Thermo-Viscoelastic Process with Irregular Viscous Dissipation (Advances in Applied Mathematics and Mechanics, 2018)
We consider a mathematical model which describes the quasi-static evolutionof a thermo-viscoelastic linear body with taking into account the effects of internalforces which generate a nonlinear viscous dissipative function. We derive a variationalformulation of the system of equilibrium equation and energy equation. An existenceresult of weak solutions was obtained in an appropriate function space.